Editorial [Hot topic: Cancer Therapy: Are we Missing the Target? (Guest Editor: Paola Gazzaniga)] - Gazzaniga, Paola (Current Cancer Drug Targets, 2010)
Targeted cancer therapies are drugs or other substances that block the growth and spread of cancer by interfering with specific molecules involved in cellular pathways which regulate tumor growth, cell proliferation or apoptosis, thus interfering with pathways that are genetically altered in tumor cells. For these drugs it is recognized that the molecular profile of the target cells predicts response. Nevertheless, recent data focus on the striking genetic disparity between primary tumors, circulating tumor cells (CTCs) and metastases, thus questioning whether the analysis of primary tumors may be really always considered as a surrogate for the genetics of systemic disease. Exemplificative is breast cancer, where it has been demonstrated that patients with HER2 negative primary tumors may develop HER2-positive CTCs during disease progression. These observed discrepancies may be the cause of tumor cell persistence and therapeutic failure in the adjuvant setting. Tumor heterogeneity is defined as the presence of intercellular differences, either from clonal origin or present within subpopulations of tumor cells; it represents a phenomenon of critical importance in the natural history of individual neoplasms. One of the main consequences of tumor heterogeneity is that locally growing and systemically spreading cancer cells show crucial genetic divergence. Thus, the predictive power for selection of targeted therapies will inevitably be imperfect and the analysis of the individual disease, in particular of the systemically spread cancer cells may be useful also for new drug combinations. The search for therapies that are specific for cancer cells has focused on differences in gene expression between normal and cancer cells. However, such differences within heterogeneous cancer cell populations must also be considered. Cellular antigens or signalling pathways expressed by cancer cells may not be optimal therapeutic targets if immature cancer stem cells that do not express the targets are also present. It is therefore essential that the development of new anticancer treatments focuses on the pathogenesis and biology of the diseases being treated in addition to the drugs and their specific targets. The collection of reviews here presented focuses on the current clinical evidence supporting the use of targeted therapies in cancer, on the molecular mechanisms involved in the development of drug resistance, and on the strategies available to overcome it. In addition, the efforts to identify new targets of minimal residual disease in melanoma are reviewed, together with the mechanisms of drug resistance frequently observed in this tumor type. Furthermore, due to the genetic discordance often described between primary tumors and metastasis and to the recent molecular characterization of circulating tumor cells, we wonder whether, in cancer treatment, we are maybe missing the right target.